High-throughput profiling the effects of zinc on antibiotic resistance genes in the anaerobic digestion of swine manure - Zhang, Ranran (Environmental technology, 2024)
The problem of antibiotic resistance genes (ARGs) caused by heavy metals has attracted extensive attention of human beings. Zn, a widely used feed additive, has a very high residue in swine manure, but the distribution characteristics of ARGs imposed by Zn in anaerobic digestion (AD) products are not clear. In this study, the behaviour of mobile genetic elements (MGEs), bacterial community, and their association with ARGs were determined in the presence of 125 and 1250 mg L-1 Zn in AD system of swine manure. Zn-treated enriched the abundance of ARGs, and produced some new genotypes that were not detected in CK treatment. In addition, low concentration of Zn significantly increased the relative abundance of ARGs, as compared to higher Zn and CK group. Correspondingly, the abundances of most top30 genus were highest in ZnL (125 mg L-1 Zn), followed by CK and ZnH (1250 mg L-1 Zn). Notably, network analysis showed that the relationship between ARGs and MGEs is closer than that ARGs and bacteria, suggesting that ARGs increased in Zn-treated, especially low level Zn, may be due to the amplification transfer of ARGs among varied microorganisms by horizontal transfer with MGEs. Therefore, strengthen the management of in livestock manure is crucial to control the spread of ARGs in organic fertilizers